Building and securing a web application with Spring Boot. (Manning Publications, 2021)
Demo of how to build and secure a web application with Spring Boot and Thymeleaf. Explore the use of Spring Initializr to initialize a new Spring Boot project, learn to write Spring controllers, and use Thymeleaf to build the UI. Use Spring Security to enable authentication and authorization in the application.